ANALISA KINERJA RUAS JALAN KALIMANTAN KOTA GORONTALO - Reren Mahmud (Universitas Bina Taruna Gorontalo, 2022)
This research was conducted on the road in Kalimantan Gorontalo City using the 1997 MKJI method. The data taken were primary data and secondary data. The Kalimantan road section is categorized as a busy road with traffic. This is because Kalimantan road is a commercial road where there are schools, settlements, cafes, supermarkets, and markets. It is known that the length of the Kalimantan road is 786.13 m, the type of road is a two-lane two-way (2/2 UD), there is no median, there is no sidewalk, there are road shoulders of approximately 0.8 - 1 m and there are drainage channels of each size. -each different. Primary data was obtained by direct observation at the research location, namely to determine the volume of vehicles, capacity, and the value of the degree of saturation. Secondary data provides data on population, road maps, and the number of vehicles in the city of Gorontalo. The time of research in the field was carried out for 3 days, namely from 14:00 – 20:00 WITA. Based on the results of traffic flow performance analysis, the maximum traffic volume calculation results occurred on Monday at 16:30 – 17:30 WITA, which was 1903.1 vehicles/hour. The value of the degree of saturation is 0.79. So the level of service on the Kalimantan road is included in category D, where the traffic flow condition is stable, the traffic speed is around 45 km/hour. The Kalimantan road section is said to be still feasible and only a few minor changes are needed, such as the need to make a sign prohibiting vehicle parking on the side of the road, especially for the shopping / stall / market area.